A Brief Study of Edward Albee: An exploration of family dynamics in Edward Albee's plays (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Albee was born on March 12, 1928 in Washington DC and was adopted by Reed and Frances Albee of New York, who were the millionaire owners of a chain of theaters. Named after his foster grandfather, Edward Franklin Albee who started this chain of theaters, Albee grew up in a world of servants but his family life left something to be desired. His mother was a stubborn lady and his father a taciturn which made the relation of the two imbalanced. Moreover, Albee’s own relationship with his parents was an awkward one. This uneasy relationship shared with his parents can be easily witnessed in the portrayal of family in his plays. C.W.E. Bigsby rightly remarks, “It is not too difficult to see in his foster-parents elements of the characters he was later to create in The American Dream” (Albee 01). In most of his plays he has coloured the husband-wife relationship as the most troubled one. Only the portrayal of Grandma in all of his plays is positive because only Grandma Cotta was the one, in his real life, who loved and understood him and with whom he really felt at home. He drew her in The American Dream and dedicated The Sandbox to her after her death in 1960.